2018
DOI: 10.1073/pnas.1715888115
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive, high-resolution binding energy landscapes reveal context dependencies of transcription factor binding

Abstract: SignificanceTranscription factors (TFs) are key proteins that bind DNA targets to coordinate gene expression in cells. Understanding how TFs recognize their DNA targets is essential for predicting how variations in regulatory sequence disrupt transcription to cause disease. Here, we develop a high-throughput assay and analysis pipeline capable of measuring binding energies for over one million sequences with high resolution and apply it toward understanding how nucleotides flanking DNA targets affect binding e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 94 publications
(149 reference statements)
8
68
0
Order By: Relevance
“…Furthermore, these features and their importance for binding may vary greatly across cell types, loci, or development timepoints 1 . Studies have shown that many of these features are related to sequence context in the immediate vicinity of the TF motif itself [14][15][16] , implying that TF binding may be predicted directly from sequence information.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these features and their importance for binding may vary greatly across cell types, loci, or development timepoints 1 . Studies have shown that many of these features are related to sequence context in the immediate vicinity of the TF motif itself [14][15][16] , implying that TF binding may be predicted directly from sequence information.…”
Section: Introductionmentioning
confidence: 99%
“…Massively parallel reporter assays (MPRAs) have made it possible to read out transcription factor binding position and occupancy in vivo with base-pair resolution, and provide a means for analyzing additional features such as "insulator" sequences [6][7][8]. In vitro methods based on protein-binding microarrays [9], SELEX [10][11][12], MITOMI [13][14][15], and binding assays performed in high-throughput sequencing flow cells [16,17] have made it possible to measure transcription factor affinity to a broad array of possible binding sites and can also account for features such as flanking sequences [15,18,19]. However, in vitro methods cannot fully account for the in vivo consequences of binding site context and interactions with other proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This would be strengthened by a tighter link between pathway mutants and transcription factor binding via traditional assays such as ChIP-seq and complementary methods such as the calling card method (Mayhew and Mitra, 2016). It would also be strengthened by incorporating the fuller understanding of the links between transcription factors and the DNA sequences they bind, both in vitro and in vivo (Le et al, 2018;Samee et al, 2019;Zhu et al, 2018). A combination of all such methods will allow us to more fully understand the role that changes in gene regulation play in evolution.…”
Section: Discussionmentioning
confidence: 99%